Justifying the Use of Lightening Drilling Mixtures Used in Drilling Low Pressure Formations - Samadov Aziz; Samadova Malika; Aziza Kasimova (Genius Journals, 2022)
In the process of drilling oil and gas wells, great requirements are placed on the properties and parameters of the drilling fluids. It is based on the fact that the wrong choice of properties and parameters of the solution in opening the formations with anomalously low formation pressure causes great complications.
Keywords: Aerated; globules; gas flow